Novel Approach for Evaluation of Bacteroides fragilis Protective Role against Bartonella henselae Liver Damage in Immunocompromised Murine Model - Pagliuca, Chiara; Cicatiello, Annunziata G.; Colicchio, Roberta; Greco, Adelaide; Cerciello, Raimondo; Auletta, Luigi; Albanese, Sandra; Scaglione, Elena; Pagliarulo, Caterina; Pastore, Gabiria; Mansueto, Gelsomina; Brunetti, Arturo; et al. (Frontiers in Microbiology, 2016)
Bartonella henselae is a gram-negative facultative intracellular bacterium and is the causative agent of cat scratch disease. Our previous data have established that Bacteroides fragilis colonization is able to prevent B. henselae damages through the polysaccharide A (PSA) in an experimental murine model. In order to determine whether the PSA is essential for the protection against pathogenic effects of B. henselae in immunocompromised hosts, SCID mice were co-infected with B. fragilis wild type or its mutant B. fragilis ΔPSA and the effects of infection on murine tissues have been observed by High-Frequency Ultrasound (HFUS), histopathological examination and Transmission Electron Microscopy (TEM). For the first time, echostructure, hepatic lobes length, vascular alterations and indirect signs of hepatic dysfunctions, routinely used as signs of disease in humans, have been analyzed in an immunocompromised murine model. Our findings showed echostructural alterations in all infected mice compared with the PBS control group; further, those infected with B. henselae and co-infected with B. henselae/B. fragilis ΔPSA presented the major echostructural alterations. Half of the mice infected with B. henselae and all those co-infected with B. henselae/B. fragilis ΔPSA have showed an altered hepatic echogenicity compared with the renal cortex. The echogenicity score of co-infected mice with B. henselae/B. fragilis ΔPSA differed significantly compared with the PBS control group (p<0.05). Moreover the inflammation score of the histopathological evaluation was fairly concordant with ultrasound findings. Ultrastructural analysis performed by TEM revealed no significant alterations in liver samples of SCID mice infected with B. fragilis wild type while those infected with B. fragilis ΔPSA showed the presence of collagen around the main vessels compared with the PBS control group. The liver samples of mice infected with B. henselae showed macro-areas rich in collagen, stellate cells and histiocytic cells. Interestingly, our data demonstrated that immunocompromised SCID mice infected with B. henselae and co-infected with B. henselae/B. fragilis ΔPSA showed the most severe morpho-structural liver damage. In addition, these results suggests that the HFUS together with histopathological evaluation could be considered good imaging approach to evaluate hepatic alterations.